2017
DOI: 10.3390/atmos8030057
|View full text |Cite
|
Sign up to set email alerts
|

Recent Enhanced Seasonal Temperature Contrast in Japan from Large Ensemble High-Resolution Climate Simulations

Abstract: Abstract:Since the late 1990s, land surface temperatures over Japan have increased during the summer and autumn, while global mean temperatures have not risen in this duration (i.e., the global warming hiatus). In contrast, winter and spring temperatures in Japan have decreased. To assess the impact of both global warming and global-scale decadal variability on this enhanced seasonal temperature contrast, we analyzed the outputs of 100 ensemble simulations of historical and counterfactual non-warming climate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Urabe and Maeda (2014) related the contrasting seasonal variations over Japan to La-Niña-like SST conditions via large-scale teleconnection, which were tied to the global surface warming slowdown. In terms of general statistics, La Niña events are associated with a high probability of cold winters and hot summers around Japan (Imada et al, 2017). That is, the relationship between the seasonal contrasts around Japan and La-Niña-like SST conditions during the slowdown period of the 2000s was qualitatively consistent.…”
Section: Air Temperatures Around Japanmentioning
confidence: 76%
See 1 more Smart Citation
“…Urabe and Maeda (2014) related the contrasting seasonal variations over Japan to La-Niña-like SST conditions via large-scale teleconnection, which were tied to the global surface warming slowdown. In terms of general statistics, La Niña events are associated with a high probability of cold winters and hot summers around Japan (Imada et al, 2017). That is, the relationship between the seasonal contrasts around Japan and La-Niña-like SST conditions during the slowdown period of the 2000s was qualitatively consistent.…”
Section: Air Temperatures Around Japanmentioning
confidence: 76%
“…During the global surface warming slowdown in 1998-2012, corresponding to the negative phase of the PDO index (1998-2013), decadal cooling and warming of land surface air temperatures in Japan was apparent for winter-spring and summer-autumn, respectively. Some studies have suggested linkages via teleconnection between Japanese air temperatures and La-Niña-like cooling in the tropical Pacific, which was tied to the global surface warming slowdown of the 2000s (Urabe and Maeda, 2014;Imada et al, 2017). Meanwhile, note that the decadal cooling of Japanese air temperatures during winter-spring occurred near the easternmost edge of the region of severe cooling in central Eurasia.…”
Section: Discussionmentioning
confidence: 99%
“…The Database for Policy Decision‐Making for Future Climate Change (d4PDF) is useful not only for future projections in extreme events (Kamae et al, ; Kawase et al, ; Mizuta et al, ; Ohba & Sugimoto, ; Osakada & Nakakita, ; Yoshida et al, ) but also for the attribution of extreme events to global warming in the twentieth century (Imada et al, ; Mizuta et al, ; Shiogama et al, ). The d4PDF includes both global climate simulations with approximately 60‐km grid spacings, which are conducted by the Meteorological Research Institute Atmospheric General Circulation Model version 3.2 (MRI‐AGCM3.2; Mizuta et al, ), and regional climate simulations with 20‐km grid spacing, which are conducted by the Non‐Hydrostatic Regional Climate Model (NHRCM; Sasaki et al, ).…”
Section: Simulation Design and Observational Datamentioning
confidence: 99%
“…Climate change may considerably influence river ice regimes (Beltaos, 2004) and consequently affect the severity of the mentioned impacts. A higher seasonal temperature contrast, which is projected by some studies at some locations (e.g., Imada et al, 2017), can increase the risk of thermal ice pressure. Increase in water level fluctuations, indicated in some rivers, e.g.…”
Section: Risk I7: Increased Load On Bridges With Control Sluice Gatesmentioning
confidence: 98%